Freedom on the offensive : human rights, democracy promotion, and US interventionism in the late Cold War - Schmidli, William Michael, 1979- (United States in the world., 2022)
"A historical analysis of the Ronald Reagan administration's (1981-1989) human rights policy, focusing on the rise of democracy promotion as a US foreign policy priority in the late Cold War, using the US intervention against the revolutionary government of Nicaragua, the Sandinista National Liberation Front (1979-1990), as the case study."--